KECURANGAN AKUNTANSI: PENGENDALIAN INTERNAL, KOMITMEN ORGANISASI, DAN ASIMETRI INFORMASI - Rahmadani, Eka; Darwanis, Darwanis (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
This study aims to influence the effectiveness of internal control, organizational commitment, and information asymmetry on accounting fraud in Banda Aceh City with the census method so that the entire population is sampled. The data in this study were collected using a survey distributing questionnaires. Respondents in this study were structural officials involved in the preparation and implementation of the budget consisting of heads of agencies, heads of finance, and treasurers in 46 SKPK of Banda Aceh City. Data analysis in this study used multiple linear regression analysis with the help of statistical software SPSS version 26. The results showed that (1) the effectiveness of internal controls, organizational commitment, and information asymmetry have a simultaneous effect on accounting fraud, (2) the effectiveness of internal controls affects accounting fraud, (3) organizational commitment affects accounting fraud, and (4) information asymmetry affects accounting fraud.